Gambaran Kesiapan Menikah pada Wanita Usia Dewasa Awal di Kelurahan Seberang Padang - Utami, Dewirza Husni; Zikra, Zikra (Lembaga Yasin AlSys, 2023)
Marriage readiness is an important thing for every couple who is getting married, because marriage readiness is a state of being ready to accept responsibility as husband and wife in every problem that will be faced in marriage. However, the phenomenon that has occurred in Indonesia in the last five years has seen a decline in marriage rates. One of the factors is that there are still many individuals who have not prepared themselves to get married from a personal or situational perspective, even though in terms of age and physique the individual is fit to get married. This research aims to describe the readiness for marriage in early adulthood women in terms of the aspect of personal readiness; have emotions that are mature and emotionally healthy, know your self-image, are of sufficient age to get married, are mature in socializing with statements of 21 items and situational readiness; financially ready and ready on time with a statement of 9 items. The method in this research uses quantitative descriptive methods. The total population in this study was 249 women in early adulthood. Sampling in this study used stratified random sampling and obtained a sample of 153 women in early adulthood in Seberang Padang Village using the Slovin formula. The scale used in this research is the Likert scale. The results of the validity test of the previously used questionnaire were 33 items, then after the validity test there were 30 valid items and 3 invalid items. Furthermore, the results of the reliability test using the Cronbach's Alpha formula were obtained (0.873), meaning that the marriage readiness questionnaire for women in early adulthood was reliable. The data analysis used in this research is descriptive-comparative analysis. The research results showed that readiness for marriage in early adulthood women in terms of personal readiness was in the medium category (58%) and situational readiness was in the high category (56%). This shows that women in early adulthood in Seberang Padang Village already have quite good readiness for marriage. Based on the results of this research, counselors can provide assistance in the form of information services and individual counseling services to help women in early adulthood increase their readiness to face marriage in the future.